2019
DOI: 10.3389/fneur.2018.01131
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Relationship Between Internal Focus and Balance Control in Young and Older Adults

Abstract: Research highlights the detrimental effect that directing too much conscious attention toward movement can have on postural control. While this concept has received support from many studies, recent evidence demonstrates that this principle does not always translate to aging clinical populations. Given the increasing clinical interest in this topic, the current study evaluated if the original notion (that an internal focus results in compromised balance performance) is upheld in young and older adults during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…This evidence is largely accrued from studies experimentally manipulating anxiety and/or attentional focus. However, in apparent contradiction, results from cross-sectional studies provide very little supporting evidence for CMP-related differences [14,15]. One potential explanation for this discrepancy may relate to the measure commonly used to assess a walker's propensity to consciously monitor and/or control their movements: the generic (non-gait-specific) Movement Specific Reinvestment Scale (MSRS) [16].…”
Section: Introductionmentioning
confidence: 99%
“…This evidence is largely accrued from studies experimentally manipulating anxiety and/or attentional focus. However, in apparent contradiction, results from cross-sectional studies provide very little supporting evidence for CMP-related differences [14,15]. One potential explanation for this discrepancy may relate to the measure commonly used to assess a walker's propensity to consciously monitor and/or control their movements: the generic (non-gait-specific) Movement Specific Reinvestment Scale (MSRS) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Vestibular function is age-dependent as above one-third of persons over 70 have an abnormal vestibular system. Vestibular nerve fibers decrease by ~5% per decade between the ages of 40 and 90, and one-third of afferents are lost after 70 [35]. However, as our studied samples had no history of vestibular dysfunction and they were below six decades, so it could be assumed that their balance control was less affected by vestibular systems dysfunction.…”
Section: Discussionmentioning
confidence: 88%
“…For example, Wulf et al (2001) demonstrated that following training young adults who had adopted an external focus of attention (i.e., keep the markers besides your feet horizontal) generated smaller balance errors than young adults who had adopted an internal focus of attention (i.e., keep your feet horizontal). Chow, Ellmers, Young, Mak, and Wong (2019) have recently compared balance performance between young adults who received internal focus instructions and young adults who received no instructions. The authors confirmed the disadvantages of adopting an internal focus of attention by showing increased body sway in young adults who were instructed to focus internally compared to participants who received no instructions.…”
Section: Introductionmentioning
confidence: 99%
“…The authors confirmed the disadvantages of adopting an internal focus of attention by showing increased body sway in young adults who were instructed to focus internally compared to participants who received no instructions. It has been argued that adopting an internal focus of attention promotes conscious movement processing, which interferes with automatic control mechanisms and, therefore, reduces fluency of movement (Wulf et al, 2001;Chow et al, 2019). Indeed, Chow et al (2019) provided objective evidence of this by demonstrating that participants who were instructed to focus internally displayed increased cortical communication between the verbal-analytical (T3) and motor planning (Fz) areas of the brain (indicative of conscious processing of the motor task; see Zhu, Poolton, Wilson, Maxwell, & Masters, 2011) compared to participants who received no instructions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation